0.19x+0.5(x-4)=0.01(2x-1)

Simple and best practice solution for 0.19x+0.5(x-4)=0.01(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.19x+0.5(x-4)=0.01(2x-1) equation:


Simplifying
0.19x + 0.5(x + -4) = 0.01(2x + -1)

Reorder the terms:
0.19x + 0.5(-4 + x) = 0.01(2x + -1)
0.19x + (-4 * 0.5 + x * 0.5) = 0.01(2x + -1)
0.19x + (-2 + 0.5x) = 0.01(2x + -1)

Reorder the terms:
-2 + 0.19x + 0.5x = 0.01(2x + -1)

Combine like terms: 0.19x + 0.5x = 0.69x
-2 + 0.69x = 0.01(2x + -1)

Reorder the terms:
-2 + 0.69x = 0.01(-1 + 2x)
-2 + 0.69x = (-1 * 0.01 + 2x * 0.01)
-2 + 0.69x = (-0.01 + 0.02x)

Solving
-2 + 0.69x = -0.01 + 0.02x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.02x' to each side of the equation.
-2 + 0.69x + -0.02x = -0.01 + 0.02x + -0.02x

Combine like terms: 0.69x + -0.02x = 0.67x
-2 + 0.67x = -0.01 + 0.02x + -0.02x

Combine like terms: 0.02x + -0.02x = 0.00
-2 + 0.67x = -0.01 + 0.00
-2 + 0.67x = -0.01

Add '2' to each side of the equation.
-2 + 2 + 0.67x = -0.01 + 2

Combine like terms: -2 + 2 = 0
0 + 0.67x = -0.01 + 2
0.67x = -0.01 + 2

Combine like terms: -0.01 + 2 = 1.99
0.67x = 1.99

Divide each side by '0.67'.
x = 2.970149254

Simplifying
x = 2.970149254

See similar equations:

| 18/x=12/28 | | 0.09Xx=105.53 | | -x^5=8 | | 4a+b=45 | | 4(5x-4)=104 | | 3a-6=-18 | | 32+x+43=180 | | 54x^2-87+35=0 | | (5-y)(3y+8)=0 | | 4a+b=27 | | 2.5x+3.75=15 | | 9ab-6a+5b-3= | | b+9+6b-9= | | 3x+11=-7+x | | 3sinx=-1.2 | | 22=7.34+b | | 2m-10+5m-80=180 | | 2(3s+6)=32 | | 4z+3-9x= | | 2k+9k= | | 8x+8=2x+3 | | y=2xy+6y-10 | | 16.95=1/x | | 5(4+2x)+2x=176 | | 3+2m-7=10 | | Y2=-1/4x | | 9x-(2x-10)=40 | | 0.5=8/x | | 4(x+6)=20x-7 | | X=112+-3x | | 7x=-26 | | 3x=146 |

Equations solver categories